Formação Docente e Autorreflexão: práticas pedagógicas coletivas de si na escola - Zamperetti, Maristani Polidori (2012)
Continuous and dynamic process, which lasts throughout life, teacher education highlights the legitimacy of professional knowledge produced by teachers and staff in their everyday work contexts. Concern about the subjectivity of the teacher and the circumstances involved in its formation as a subject are part of the motivation that led to this investigation. "Teacher Education and Self-reflection, self-pedagogic collective practices of the school" emerges from the processes experienced by the teacher-researcher who has investigated the possibility of the existence or construction of spaces reflexive in EMEF Almirante Raphael Brusque in Pelotas, RS. To do so, in search of theoretical Barbier (2007) and Larrosa (2000), subsidies that identify the action research conducted in the school as a self-pedagogic practice, with a focus on collaborative research and studies on teacher education, offered by Porto (2001, 2003) and Nóvoa (1997, 2009). This research were offered experiences with artistic practices in processes of teacher education, promoting oxygenation and the creation of spaces of experience, organization of collective work, reflection and self-education in school. Combined records in the field notebook, photographs, audio recordings, transcripts of meetings and written reports by teachers, artistic productions were gathered as evidence and research data. The research showed the possibility of creating spaces for themselves and experience the production of reflexive relations, which allow the redefinition of practice and teacher education within the school. I conclude from these findings that the relationship between knowledge of self and collective experiences allow teachers to reflect on the teaching status.